2016
DOI: 10.1038/srep39412
|View full text |Cite
|
Sign up to set email alerts
|

Plasma DPP4 activity is associated with no-reflow and major bleeding events in Chinese PCI-treated STEMI patients

Abstract: Dipeptidyl peptidase-4 (DPP4) is an important regulator of incretins and inflammation, and it is involved in the pathophysiological process of myocardial infarction (MI). This study investigated the role of plasma DPP4 activity (DPP4a) in patients with ST-segment elevation myocardial infarction (STEMI) who had undergone percutaneous coronary intervention (PCI). We recruited 747 consecutive PCI-treated STEMI patients from a tertiary referral center from January 2014 to October 2015. The outcomes of interest wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…However, in our study cohort, no significant correlation was detected between BMI and serum DPP4 activity. This is in accordance with previous findings in STEMI patients, in whom no difference was detected in BMI among different quartiles of plasma DPP4 activity 39 , 54 . In contrast, as mentioned earlier, patients with a recent myocardial infarction exhibited a significantly reduced pre-operative DDP4 activity when compared to patients without recent infarction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in our study cohort, no significant correlation was detected between BMI and serum DPP4 activity. This is in accordance with previous findings in STEMI patients, in whom no difference was detected in BMI among different quartiles of plasma DPP4 activity 39 , 54 . In contrast, as mentioned earlier, patients with a recent myocardial infarction exhibited a significantly reduced pre-operative DDP4 activity when compared to patients without recent infarction.…”
Section: Discussionsupporting
confidence: 93%
“…Further, DPP4 activity decreased during cardiac surgery with CPB, if not already decreased by a recent myocardial infarction or severely reduced LVEF. Although this contrasts earlier experimental findings of hypoxia-induced shedding of membrane DPP4 from vascular cells 20 , 55 , our findings are in line with a clinical study in STEMI patients showing reduced plasma DPP4 activity after myocardial infarction 54 . Also, hypoxia treatment of adipocytes significantly reduced the activity of shedded DPP4 56 , although the underlying mechanisms remained unclear.…”
Section: Discussionsupporting
confidence: 66%
“…Although a previous study has shown that DPP4a was higher in diabetic populations [ 12 , 31 ], this trend was not observed in the current study. However, DPP4a is reduced after MI [ 13 ], thus diabetic patients may have more severe DPP4a reductions after STEMI than non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fast plasma glucose, total cholesterol, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides, N-terminal pro B-type natriuretic peptide (NT-proBNP), creatinine, creatine kinase-MB (CK-MB), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyltransferase (GGT) levels were measured using automated enzymatic methods (Cobas ® , Roche, Germany). DPP4 activities were determined in EDTA-treated plasma samples by measuring rates of p-nitroaniline (pNa) cleavage from the synthetic substrate H-Gly-Pro-pNa (L1880, Bachem, Switzerland) by DPP4, as previously described [ 13 ]. Briefly, 5 µL plasma samples were added to 150 µL of 50 mM tris–HCl containing 1 mM H-Gly-Pro-pNa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation